TINJAUAN ATAS SISTEM INFORMASI AKUNTANSI PENAGIHAN PIUTANG PADA PT. PERTAMINA LUBRICANTS - Luthfi Sardi (2020)
The Final Assignment Report aims to learn more about the use of accounting information systems for the collection of accounts receivable payments in the world of work. This Final Project has a specific goal which is to qualify for graduation from the Third Diploma (DIII) program for accounting major at the Veteran national development university of jakarta. In carrying out the Field Work Practice has many benefits, one of which is to add insight and hone the capabilities possessed in the real work world. The author chooses the location of the Field Work Practice at PT. Pertamina Lubricants whose address is at Floor Kav.55, Oil Center, Jalan M.H. Thamrin, RT.6, Gondangdia, RT.9 / RW.5, Gondangdia, Kec. Menteng, Kota Jakarta Pusat. PT. Pertamina Lubricants is a manufacturing company engaged in the production of lubricants and also a provider of Oil Clinic services. Lubricants produced are useful for industrial machinery and vehicles. During carrying out Field Work Practices activities, the author is placed in the finance (Treasury). The tasks undertaken in the Field Work Practice are to confirm debt payments, fill out documents, check the completeness of Sp3 documents, and study the receivables cycle. After carrying out the Job Training can draw the conclusion that the existence of the Job Training makes the student's mentality improve to be more confident in the world of work and gain experience in the world of work. So it becomes a provision of knowledge for writers to enter the workforce.